On g_α-Grill in Topological Spaces - Thivagar, M. Lellis; Paul, Nirmala Rebecca (Journal of Informatics and Mathematical Sciences, 2012)
The aim of this paper is to introduce a new type of topology in terms of grills and g_α-sets and study the related topological properties. We define new types of sets to study the relationship between the new sets and existing sets and to derive a new decomposition of continuity.